Implementation of Problem-Based Learning Model in Improving Speaking Skills for Part-Time Students at A Higher Education Institution in Semarang - Hamsia, Waode; Erydani, Vinsensia Anisa Citta (Institut Agama Islam Negeri Kudus, 2022)
The ability to communicate verbally is considered to be one of the important factors for basic language skills. This competency plays a significant role in oral communication. The purpose of this study was to determine whether or not the use of a model called Problem-Based Learning (PBL) might help students enhance their speaking ability. PBL is one of the learning models that can be used in language classes because the focus of the learning model is involving students in the learning process. The PBL model encourages meaningful interactions for the working students who study in part-time class as the special program. Since the students must be trained to practice speaking English. Therefore, speaking competence can be achieved through the activities. Observation and a questionnaire were the two techniques that were used to collect the data. The results showed that the PBL model used by the lecturer in the teaching and learning process that focuses on the discussion to get the alternative solution deeply can make students understand every detail in practicing speaking with real-life issues that require real-life solutions. Thus, this study implied that PBL as a learning model for English subjects was appropriate to make students fluent to communicate in English